USP Reference Standard Monoclonal Antibodies: Tools to Verify Glycan Structure - Jingzhong Guo; Huiping Tu; Li Jing; Diane McCarthy; Fouad Atouf (MDPI AG, 2022)
The glycan profile is a critical quality attribute for pharmaceutical monoclonal antibodies due to the potential physiological impact of the glycan composition when used as a drug product. Monoclonal antibody reference standards are useful as system suitability samples for glycan profile testing. The development of future glycan profiling techniques could be better evaluated by testing well-characterized reference standards. The USP has introduced monoclonal antibody reference standards (i.e., USP mAb 001 RS, USP mAb 002 RS, and USP mAb 003 RS) with the glycan profiles reported herein that can be used to assess the analytical testing of monoclonal antibody glycan profiles. Comparison of the USP reference standards to other available reference standards (NISTmAb) is presented. The glycan profile of the USP monoclonal antibody reference standards covers a range of glycan species that complements other available reference standards. The USP mAb reference standards are a valuable tool that can be used to verify the glycan structure and provide the system suitability of analytical methods.